A Typological Reading of Prevailing Legal Theories. (June 2014) - Novak, Marko
Abstract A classic debate in the history of philosophy is that between rationalists and empiricists concerning the "true" source of human knowledge. In legal philosophy this debate has been reflected in the classic opposition between natural law and legal positivist perspectives. Even the currently predominant inclusivist perspectives on the nature of law, such as inclusive legal positivism and inclusive legal non‐positivism, are not immune to such a dichotomy. In this paper I attempt to present an understanding of specific cognitive characteristics of prevailing legal theories from the perspective of the theory of psychological types as developed by Carl G. Jung.